'Armailt làidir de mhilìsidh': Hanoverian Gaels and the Jacobite Rebellion of 1745. Issue 2 (August 2021) - Dziennik, Matthew
Abstract : In 1745–6, thousands of troops were raised in the Highlands and Islands in support of the house of Hanover. Often neglected due to the intense focus on Highland Jacobitism, these Gaels were instrumental in the defeat of the Jacobites. The study of pro-Hanoverian forces in the Gàidhealtachd tells us much not only about the military history of the 1745 rebellion but also about the nature of the whig regime in Scotland. In contrast to the ideological frameworks increasingly used to make sense of the Jacobite period, this article argues that pragmatic negotiations between the central government and the whig clans helped mobilise and empower regional responses to the rebellion. Exploiting the government's need for Gaelic allies in late 1745, Highland leaders, officers, and enlisted men used military service to shore up a nexus of political, financial and security imperatives. By examining the recruitment and service of anti-Jacobite Gaels, this article shows that—even in the epicentre of the rebellion—the Hanoverian state possessed important structural strengths that enabled it to confront the threat of armed insurrection. In so doing, the article reveals the political and fiscal-military networks that sustained whig control in Scotland.